A method for selective lithium extraction and fluorine fixation by dry roasting sodium sulfate in cooperation with calcium carbonate

CN122897426APending Publication Date: 2026-10-13GUIQIU HUANENG TECHNOLOGY (HUNAN) CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611378227.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-07
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

[0008]本发明的目的在于提供一种硫酸钠协同碳酸钙干法焙烧选择性提锂并固氟方法,以解决现有工艺使用液态浓硫酸导致腐蚀性强、含氟气体控制困难、石墨需要另行去除以及锂与铁磷分离流程较长的问题

Benefits of technology

[0019](1)采用固体无水硫酸钠作为硫酸化剂,避免将液态浓硫酸直接加入黑粉,从源头降低强酸腐蚀和操作安全风险。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122897426A_ABST
    Figure CN122897426A_ABST
Patent Text Reader

Abstract

The application discloses a method for selectively extracting lithium and fixing fluorine by dry calcination of sodium sulfate and calcium carbonate, and belongs to the field of recycling of waste lithium ion batteries. Black powder containing lithium iron phosphate, fluorine-containing electrolyte residues and graphite is mixed with anhydrous sodium sulfate and calcium carbonate in a dry manner, and then calcined at 500-650 DEG C for 2-8 hours in an oxidizing atmosphere, so as to promote the conversion of lithium into water-soluble lithium sulfate, the oxidation of graphite and organic matters, and the transfer of fluorine to a calcium-containing solid phase; the calcined clinker is subjected to water immersion, solid-liquid separation, impurity removal by pH adjustment and lithium precipitation by sodium carbonate, so as to obtain a lithium carbonate product. The application does not need to use liquid concentrated sulfuric acid, and can simultaneously extract lithium, remove carbon and fix fluorine in the same calcination step.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of waste lithium-ion battery recycling and resource comprehensive utilization technology, specifically to a method for selectively extracting lithium and simultaneously solidifying fluorine by dry roasting waste lithium iron phosphate battery black powder under an oxidizing atmosphere using solid sodium sulfate as a sulfation agent and calcium carbonate as a fluorine-fixing agent. Background Technology

[0002] With the development of new energy vehicles and the energy storage industry, the number of retired lithium iron phosphate batteries continues to increase. Although lithium iron phosphate batteries do not contain high-value metals such as cobalt and nickel, the lithium in them has high recycling value; at the same time, the electrolyte usually contains fluorine-containing substances such as lithium hexafluorophosphate, and improper disposal may cause fluorine pollution. Therefore, it is necessary to develop a treatment process that takes into account both lithium recovery and the harmless treatment of fluorine-containing components.

[0003] Existing wet recovery methods typically involve acid leaching to introduce lithium, iron, and phosphorus components into a solution, followed by separation through neutralization, precipitation, or extraction. This process suffers from several drawbacks, including high acid and alkali consumption, low lithium-ion concentration in the leaching solution requiring high-energy concentration, low pH in the leaching solution necessitating large amounts of alkali to raise the pH, significant wastewater volume, and lengthy lithium-iron-phosphorus separation processes. While the sulfation roasting-water leaching process can convert lithium into water-soluble sulfates, the use of concentrated liquid sulfuric acid presents challenges such as high corrosivity and stringent operational safety requirements. Furthermore, residual fluorine-containing components in the black powder may generate fluorine-containing gases upon heating, increasing the burden on equipment corrosion prevention and exhaust gas treatment.

[0004] Another approach is the reduction roasting-water immersion route, which uses an external carbon source or graphite from black powder to create reduction conditions. This route requires control of the reducing agent ratio and reducing atmosphere. The roasted carbonaceous material may also increase the burden on subsequent separation, and it is difficult to ensure the stable solidification of fluorine-containing components in the same roasting step.

[0005] Chinese patent application CN117185319A discloses a method for recovering lithium iron phosphate batteries by sulfate air roasting. In this method, lithium iron phosphate powder is mixed with ammonium sulfate, sodium sulfate, potassium sulfate, or magnesium sulfate, and then air-roasted at 400-800°C for 4-6 hours, followed by water leaching and carbonate precipitation. This technology, like the present invention, belongs to the sulfate roasting-water leaching lithium extraction route and can be considered a relatively close prior art. However, its processing mainly targets the separated lithium iron phosphate powder, and does not address the mixed black powder containing both negative electrode graphite and fluorine-containing electrolyte residues. Furthermore, it does not disclose a technical solution for adding calcium carbonate during atmospheric pressure oxidative roasting to simultaneously fix fluorine and reduce residual carbon.

[0006] Chinese patent CN114132951B discloses a method for extracting lithium from waste lithium battery black powder through pressure roasting and fluoride fixation. It uses CaO, Ca(OH)₂, or CaCO₃ as the fluoride fixation agent, roasting at 0.3–2.0 MPa and 600–1200 °C, and then proceeds with lithium extraction by introducing carbon dioxide. This technology demonstrates that calcium-based fluoride fixation agents can convert fluorine-containing components into a poorly soluble calcium-containing solid phase. However, its targets are mainly lithium nickel cobalt manganese oxide, lithium cobalt oxide, lithium manganese oxide, or lithium nickel cobalt aluminum oxide black powder, and it relies on pressure roasting and carbonization steps. It does not disclose the synergistic lithium extraction, carbon removal, and fluoride fixation of anhydrous sodium sulfate and calcium carbonate in the atmospheric pressure oxidative roasting of mixed lithium iron phosphate black powder.

[0007] Therefore, there is a need for a selective lithium extraction method that does not require liquid concentrated sulfuric acid, can simultaneously remove graphite and organic matter in an oxidizing atmosphere, and fix fluorine during the calcination stage, in order to shorten the process and reduce the risk of corrosion and fluorine-containing gas escape. Summary of the Invention

[0008] The purpose of this invention is to provide a selective lithium extraction and fluorine fixation method using sodium sulfate and calcium carbonate dry roasting, which solves the problems of strong corrosiveness, difficulty in controlling fluorine-containing gases, the need for separate removal of graphite, and the long lithium-iron-phosphorus separation process in existing processes that use liquid concentrated sulfuric acid.

[0009] To achieve the above objectives, the present invention provides a method for selective lithium extraction and fluorine fixation via dry roasting of sodium sulfate and calcium carbonate, comprising the following steps:

[0010] S1. Raw material preparation: Discharge, disassemble, crush and screen the waste lithium iron phosphate batteries to obtain black powder containing lithium iron phosphate, fluorine-containing electrolyte residue, negative electrode graphite, conductive agent and binder; wherein, the total mass of lithium iron phosphate and fluorine-containing electrolyte residue accounts for 45% to 55% of the mass of black powder, and negative electrode graphite accounts for 40% to 55% of the mass of black powder.

[0011] S2. Ingredient Mixing: Determine the total molar amount of lithium and fluorine in the black powder. Add anhydrous sodium sulfate at a molar ratio of lithium to anhydrous sodium sulfate of 1:(0.9~1.2), and add calcium carbonate at a molar ratio of fluorine to calcium carbonate of 1:(0.9~1.2). Mix the three ingredients dry to obtain a mixture. Preferably, both molar ratios are 1:1.

[0012] S3. Calcination and Conversion: The mixture is placed in a rotary kiln and calcined at 500-650℃ for 2-8 hours in an oxidizing atmosphere formed by air or oxygen-containing gas to obtain calcined clinker. During this process, the negative electrode graphite and organic matter are oxidized, lithium is converted into water-soluble lithium sulfate, and fluorine is transferred to the calcium-containing solid phase; iron and phosphorus are mainly retained in the insoluble iron phosphate phase.

[0013] S4. Water leaching and filtration: Water is added to the roasted clinker, stirred, and leached, followed by solid-liquid separation to obtain a mother liquor containing lithium sulfate and a filter residue containing a sparingly soluble iron phosphate phase, a calcium- and fluorine-containing solid phase, and ash. The volume ratio of water to the mass of the roasted clinker is preferably 1~6 mL / g, the leaching temperature is preferably 40~80℃, and the leaching time is preferably 20~60 minutes.

[0014] S5. Purification: An alkaline substance is added to the mother liquor containing lithium sulfate to adjust the pH to 7-11, causing at least some aluminum, iron, and calcium impurities to precipitate or separate together with the remaining insoluble matter. After solid-liquid separation, a purified lithium sulfate solution is obtained. The alkaline substance can be sodium carbonate, sodium hydroxide, or a combination of both, preferably adjusting the pH to 8-11.

[0015] S6. Lithium Precipitation Purification: A saturated sodium carbonate solution is added to the purified lithium sulfate solution to initiate a lithium precipitation reaction. Solid-liquid separation, washing, and drying are then performed to obtain the lithium carbonate product. The theoretical amount of lithium precipitation is calculated based on the measured total molar amount of lithium in the purified lithium sulfate solution, with 1 mole of sodium carbonate corresponding to every 2 moles of lithium. The preferred amount of saturated sodium carbonate solution added is 1.05 to 1.3 times the theoretical amount. The preferred precipitation temperature is 80 to 95°C, and the preferred precipitation time is 0.5 to 2 hours.

[0016] In some embodiments, the total mass of lithium iron phosphate and fluorine-containing electrolyte residue in the black powder accounts for 30% to 60% of the black powder mass, and the negative electrode graphite accounts for 20% to 60% of the black powder mass; preferably, the former is 45% to 55% and the latter is 40% to 55%.

[0017] In some implementations, a high-speed mixer is used to dry mix the black powder, anhydrous sodium sulfate, and calcium carbonate for 20 minutes.

[0018] Compared with the prior art, the present invention has at least the following beneficial effects:

[0019] (1) Solid anhydrous sodium sulfate is used as a sulfation agent to avoid adding liquid concentrated sulfuric acid directly to black powder, thereby reducing the risk of strong acid corrosion and operational safety from the source.

[0020] (2) Calcium carbonate provides a calcium-containing reaction phase for fluorine-containing components during the roasting process, which promotes the transfer of fluorine to the calcium-containing solid phase and helps reduce the risk of fluorine entering the leaching mother liquor and migrating with the gas phase; the actual fluorine fixation effect is verified by the phase analysis of the filter residue and the fluorine element balance.

[0021] (3) Roasting in an oxidizing atmosphere formed by air or oxygen-containing gas promotes the oxidation of negative electrode graphite and organic matter, which is beneficial to reducing the residual carbon content of roasted clinker; the actual carbon removal effect is evaluated by the total carbon content measured before and after roasting.

[0022] (4) Lithium is converted into water-soluble lithium sulfate and enters the mother liquor. Iron, phosphorus and calcium- and fluorine-containing solid phases are mainly retained in the filter residue, thus forming a selective separation path between lithium and iron, phosphorus and fluorine. The actual separation effect is verified by the elemental balance between the liquid phase and the solid phase.

[0023] (5) The preferred roasting temperature is 500~650℃, which takes into account lithium conversion, carbon removal and solid fluorine treatment in a shorter process; the total lithium recovery rate reported in Examples 1~3 is 86.0%~95.1%, and the main lithium carbonate content is 98.5%~99.6%. Battery-grade products still need to be judged according to all indicators of YS / T582-2023.

[0024] (6) The process is mainly dry roasting and supplemented by wet separation. The filter residue may contain insoluble iron phosphate phase, calcium and fluorine solid phase and ash, which is convenient for subsequent resource utilization or stabilization treatment.

[0025] (7) The process does not use concentrated sulfuric acid leaching, which avoids the low pH value in the leaching solution and the consumption of a large amount of alkali to raise the pH value; it also avoids the need for a high-energy-consuming concentration process for low-concentration lithium ions in the acid leaching solution, thus reducing acid and alkali consumption and concentration energy consumption. Attached Figure Description

[0026] Figure 1 This is a process flow diagram of the selective lithium extraction and fluorine fixation method using sodium sulfate and calcium carbonate dry roasting according to the present invention.

[0027] Figure 2 This is a schematic diagram of the material transformation and fluorine curing mechanism during the calcination stage of this invention.

[0028] Figure 3 The graph shows the results of lithium leaching rate and fluorine fixation rate of filter residue in Example 1 of the present invention. Detailed Implementation

[0029] The present invention will be further described below with reference to the accompanying drawings and embodiments. The following embodiments are used to illustrate the technical solutions of the present invention and are not intended to limit the scope of protection of the present invention. Unless otherwise stated, all raw materials and reagents used can be industrial-grade raw materials or analytical-grade reagents, and all percentages are mass percentages.

[0030] The term "black powder" as used in this invention refers to a powder mixture obtained after waste lithium iron phosphate batteries have undergone discharge, dismantling, crushing, and sieving. It typically contains residual lithium iron phosphate, negative electrode graphite, conductive agents, binders, and electrolytes such as lithium hexafluorophosphate. Depending on the degree of pretreatment, the black powder may also contain small amounts of aluminum, copper, and their compounds.

[0031] The "oxidizing atmosphere" referred to in this invention refers to an atmosphere capable of oxidizing the graphite and organic matter in the black powder during the calcination process, including air and mixed gases containing oxygen. An oxidizing atmosphere can be formed through natural air intake or controlled air supply in a rotary kiln.

[0032] Before batching, a representative sample of the black powder was taken, and the lithium and fluorine contents were determined and converted into total molar amounts. Lithium could be determined by inductively coupled plasma atomic emission spectrometry (ICP) after sample digestion; fluorine could be determined by ion chromatography or fluoride ion selective electrode method after appropriate pretreatment. The detection methods used should be calibrated or validated in the corresponding sample matrix and should be able to obtain the total lithium and fluorine amounts used for batching calculations.

[0033] To ensure the technical effectiveness can be repeatedly verified, representative samples from the black powder, roasted clinker, leaching mother liquor, washing liquid, filter residue, and lithium carbonate product were subjected to elemental analysis. The total lithium recovery rate was calculated as the ratio of the mass of lithium in the lithium carbonate product to the mass of lithium in the initial black powder. The lithium leaching rate was calculated as the ratio of the total mass of lithium in the leachate and washing liquid to the total mass of lithium in the roasted clinker entering the leaching process. When the washing liquid was incorporated into the leachate, the total mass of lithium in the combined liquid was used for calculation. Lithium, sodium, iron, phosphorus, and calcium in the liquid phase were determined using inductively coupled plasma atomic emission spectrometry (ICP-AES), and the solid samples were determined using the same method after digestion, thus establishing a material balance for lithium, sodium, iron, phosphorus, and calcium.

[0034] The fluoride fixation effect can be evaluated through a combination of phase identification and fluoride elemental balance: X-ray diffraction analysis is used to identify calcium-containing solid phases such as calcium fluoride in the filter residue; the total fluoride in the filter residue is determined according to relevant environmental standards; the filter residue leachate is prepared using the horizontal oscillation method (or sulfuric acid-nitric acid method), and the fluoride concentration in the leachate is determined using ion chromatography or fluoride ion selective electrode method. The fluoride fixation rate of the filter residue is calculated as the ratio of the mass of fluoride in the filter residue to the total mass of fluoride brought into the roasting-leaching system by the initial black powder. The input stream for the fluoride elemental balance is the initial black powder, and the output stream includes the filter residue, leachate, and washing liquid; when collectable dust and fluoride-containing tail gas are generated during the roasting process, the output stream also includes recovered dust and tail gas absorbent. When the washing liquid is incorporated into the leachate, the total mass of fluoride in the combined liquid is included in the balance.

[0035] The carbon removal effect can be determined by combustion-infrared absorption or elemental analysis to measure the total carbon mass fraction of the mixture before roasting and the roasted clinker. The total carbon mass at each stage is calculated as the product of the total mass of the corresponding material and the total carbon mass fraction; the carbon removal rate is calculated as the percentage of the difference between the total carbon mass before roasting and the residual total carbon mass after roasting to the total carbon mass before roasting. When the residual carbon is below the detection limit of the method used, it is reported as not detected and the detection limit is noted; otherwise, the residual carbon content or carbon removal rate is reported.

[0036] Based on the feed disclosed in Example 1, the initial lithium was approximately 11.01 kg and fluorine was approximately 9.39 kg; after adding anhydrous sodium sulfate, approximately 72.97 kg of sodium and 50.89 kg of sulfur were introduced; after adding calcium carbonate, approximately 19.80 kg of calcium was introduced. Based on 237.5 kg of lithium iron phosphate, approximately 84.1 kg of iron and 46.6 kg of phosphorus were estimated; the initial graphite was approximately 250 kg. The accurate feed amount of carbon was corrected based on the measured total carbon value. Table 1 is used to illustrate the sampling and detection scheme for elemental balance and does not represent the measured distribution rate or balance closure rate of each element; the elemental mass and distribution ratio in each product stream must be sampled and measured according to Table 1, and theoretical reaction formulas should not replace measured results.

[0037] Table 1 shows the sampling locations, detection methods, and accounting indicators for elemental balance:

[0038] Li 1587 mol, approximately 11.01 kg Purification liquid, lithium carbonate products; small amounts enter filter residue and mother liquor at each stage. Black powder, clinker, leachate, filter residue, purification residue, products, lithium precipitation mother liquor Solid digestion / liquid dilution followed by ICP-OES Lithium leaching rate, total lithium recovery rate, and Li balance closure rate F 494 mol, approximately 9.39 kg The main component enters the calcium-containing filter residue; a small amount enters the mother liquor and tail gas absorption liquid. Black powder, filter residue, leachate, washing liquid, and tail gas absorption liquid Total fluoride was determined by alkali fusion-ion chromatography or fluoride ion selective electrode method; aqueous fluoride was determined by ion chromatography or fluoride ion selective electrode method; XRD was used for auxiliary phase confirmation. Fluorine fixation rate of filter residue and F balance closure rate Na 3174 mol, approximately 72.97 kg It mainly enters the water leaching solution, purification solution, and lithium precipitation mother liquor; a small amount enters the filter residue and product entrainment. Sodium sulfate, filter residue, liquid phases at various stages, and products ICP-OES or flame atomic absorption spectrometry Na balance closure rate and Na impurities in the product S 1587 mol, approximately 50.89 kg The main form of sulfate ions enters the leachate and lithium precipitation mother liquor; a small amount remains in the filter residue, product, or washing solution. Sodium sulfate, filter residue, liquid phases at various stages, and products Ion chromatography, barium sulfate turbidimetric method or ICP-OES S-balance closure rate and sulfate impurities in the product Ca 494 mol, approximately 19.80 kg The main component enters the calcium-containing solid fluoride phase and is used for impurity removal; a small amount enters the mother liquor and products. Calcium carbonate, filter residue, purification residue, various liquid phases, products ICP-OES; XRD-assisted confirmation of calcium-containing phases Ca balance closure rate and Ca impurities in the product Fe, P Based on lithium iron phosphate, the estimated Fe content is approximately 84.1 kg and the P content is approximately 46.6 kg. It mainly enters the filter residue containing sparingly soluble iron phosphate and the impurity removal residue. Black powder, filter residue, purification residue, various liquid phases, and products ICP-OES; XRD-assisted confirmation of solid phase Fe and P balance closure rate and liquid phase / product impurities C Approximately 250 kg of graphite; corrected by measured total carbon. The main oxidation process enters the exhaust gas; the residue remains in the clinker and filter residue. Black powder, clinker, and filter residue; measure tail gas CO2 if necessary. Combustion-infrared absorption method or elemental analysis method Carbon removal rate and C balance closure rate

[0039] The elemental balance closure rate is calculated as the ratio of the sum of the masses of the element in each output stream to the mass of the element in the input stream. The total amount of each solid and liquid stream is first weighed or measured, and then the mass fraction or concentration of the element is determined; at least two parallel samples are taken. In industrial trials, 90%–110% is preferably considered the effective balance closure range; if it exceeds this range, the representativeness of the sampling, dust recovery, tail gas absorption, and liquid metering are rechecked, and the balance result is determined after verification. Quantitative evaluation of the solid fluoride rate, recovery rate, and elemental distribution ratio uses data where the balance closure rate falls within the aforementioned effective range.

[0040] Process principle and operation method:

[0041] like Figure 1 As shown, the method of the present invention sequentially includes raw material preparation S1, ingredient mixing S2, roasting and conversion S3, water immersion and pressure filtration S4, impurity removal and purification S5, and lithium precipitation purification S6. In S1, black powder is obtained from waste lithium iron phosphate batteries; in S2, anhydrous sodium sulfate and calcium carbonate are added according to the total molar amount of lithium and fluorine in the black powder and dry-mixed; in S3, roasting is carried out under an oxidizing atmosphere to convert lithium into water-soluble lithium sulfate, and graphite and organic matter undergo oxidation, and promote the transfer of fluorine to the calcium-containing solid phase; in S4, lithium-containing mother liquor and filter residue mainly containing insoluble iron phosphate phase, calcium-containing fluorine solid phase and ash are obtained through water immersion and solid-liquid separation; in S5, the pH of the mother liquor is adjusted and solid-liquid separation is carried out to obtain a purified lithium-containing solution; in S6, sodium carbonate is added to precipitate lithium, and lithium carbonate product is obtained after solid-liquid separation, washing and drying. Figure 1 The dashed line below represents the solid fluoride control strategy that runs through the batching, roasting, solid-liquid separation and subsequent liquid phase treatment. That is, calcium carbonate is used to provide a calcium-containing reaction phase to reduce the risk of fluoride entering the leachate and gas phase. This dashed line is a schematic diagram of the mechanism and does not mean that each step involves an independent fluorination reaction, nor does it represent the measured element flow rate.

[0042] Under oxidizing roasting conditions, the ferrous iron in lithium iron phosphate undergoes oxidation, accompanied by lithium extraction. The sulfate ions provided by sodium sulfate react with the extracted lithium to form water-soluble lithium-containing sulfates. Iron and phosphorus primarily enter the insoluble iron-containing phosphate phase. Due to differences in the composition of the black powder and the degree of roasting, sodium may exist in the residual sodium sulfate, water-soluble sodium salt, or sodium-containing phosphate phase, and will be distributed between the liquid and solid phases during subsequent water leaching. Therefore, the roasting process may include multiple parallel solid-phase reactions, and its phase transformation is not represented by a single reaction equation. Calcium carbonate provides calcium, which interacts with fluorine-containing components, promoting the entry of fluorine into the calcium- and fluorine-containing solid phase. Whether this solid phase contains calcium fluoride and the actual distribution of each element are verified using X-ray diffraction analysis and elemental balance results.

[0043] like Figure 2 As shown, the mixture before calcination may contain lithium iron phosphate, residual fluorinated electrolyte, negative electrode graphite, conductive agent or binder, anhydrous sodium sulfate, and calcium carbonate. After calcination in air or oxygen-containing gas at 500-650°C for 2-8 hours, the calcination products may include a water-soluble lithium sulfate phase, a sparingly soluble iron phosphate phase, a calcium- and fluorine-containing solid phase, and gaseous products such as carbon dioxide and water vapor. Figure 2 The right side illustrates a possible pathway for the decomposition or transformation of fluorine residues to produce fluorine-containing species, and for calcium carbonate to form a reactive calcium-containing phase and capture fluorine. In the diagram, CaO represents the reactive calcium-containing phase, and CaO + 2HF → CaF2 + H2O represents a schematic reaction. This diagram does not indicate that only the shown calcium-containing phase or only the shown reaction occurs during the calcination process. The presence of CaF2 in the calcination product and the composition of each calcium- and fluorine-containing phase will be determined by X-ray diffraction analysis and fluorine elemental balance.

[0044] In step S1, the discharge operation is used to reduce the safety risks of disassembly; after disassembly, crushing and sieving are performed to allow the positive and negative electrode active materials, electrolyte residues, and conductive agents to enter the black powder. The sieving particle size can be determined based on the subsequent mixing and calcination equipment, with the aim of achieving uniform batching and stable feeding.

[0045] In step S2, the ingredients are prepared based on the total molar amount of each element to accommodate compositional fluctuations in retired batteries from different sources; both molar ratios are process feed ratios. Based on theoretical calculations for the formation of Li₂SO₄ and CaF₂, the required amount of anhydrous sodium sulfate per mole of lithium and calcium carbonate per mole of fluorine is 0.5 mol. Therefore, 0.9 times and 1.2 times the feed amounts are 1.8 times and 2.4 times the theoretical stoichiometric requirements, respectively. Considering only the amount of reactants and assuming complete reaction, the corresponding theoretical upper limit of lithium sulfate conversion and fluorine binding capacity is 100%. 500 ℃ and 650 ℃ do not change this upper limit, but they will affect phase transformation, solid-phase mass transfer, and fluorine-containing species migration. Therefore, the 100% is not considered as the measured result of lithium leaching rate or fluorine fixation rate in filter residue; the actual values ​​are determined according to the aforementioned sampling, detection, and elemental balance methods. Mixing can be performed using a high-speed mixer, a plow mixer, or other powder homogenization equipment.

[0046] In step S3, the mixture is continuously or intermittently fed into a rotary kiln and calcined at 500-650℃ for 2-8 hours. Calcination temperature and time both affect the solid-phase reaction and the degree of graphite oxidation: lower temperatures allow for longer calcination times, while higher temperatures shorten the calcination time. After calcination, the material is cooled to obtain calcined clinker. A reducing atmosphere should be avoided to prevent weakening the oxidation and removal of graphite and organic matter.

[0047] For industrial-scale implementation, a continuous rotary kiln can be used, with a preheating section, a 500-650℃ roasting section, and a cooling section along the kiln body. After mixing the ingredients, at least five samples are taken from different locations to form a mixed sample, and the lithium, sodium, and calcium contents are determined. A uniform mixture is considered to have a relative standard deviation of no more than 5% for each sample. The volumetric filling rate of the material in the rotary kiln is controlled to be no more than 20% of the effective volume, and the rotation speed is 1-10 r / min, preferably 2-4 r / min. Air is supplied at a volume of 50-200 times the effective volume of the rotary kiln per hour, and air can be supplied in sections at the kiln head, middle, and tail to maintain an oxidizing atmosphere in the roasting section. During continuous operation, the average residence time of the material in the 500-650℃ roasting section is taken as 2-8 hours. Temperature measuring points are arranged along the front, middle, and rear of the roasting section, and the deviation of the actual temperature at each measuring point from the set value is preferably no more than 10℃. When operating intermittently, the temperature can be increased at a rate of 2~10℃ / min until the set temperature is reached, and then the holding time can be calculated.

[0048] Maintaining a slight negative pressure inside the kiln and preventing dust and flue gas from escaping into the workshop are control requirements. The roasting exhaust gas undergoes sequential treatment via cyclone separation or sedimentation, baghouse dust collection, and alkaline absorption. Collected dust is returned to the batching or clinker leaching process. The alkaline absorption liquid can be calcium hydroxide or calcium oxide slurry, and fluorine balance is taken into account. The airflow, rotation speed, or feed rate is adjusted based on the detection results of residual oxygen in the exhaust gas and residual carbon in the clinker. After the roasted clinker is cooled to below 80°C, it is conveyed to the leaching process in a sealed manner. The leaching tank volume is configured according to a water-to-material ratio of 1~6 mL / g; the leaching tank, filter press, and mother liquor storage tank are all set according to the single batch material quantity and a 10%~20% operating margin. The above equipment parameters are optional operating conditions for industrial scale-up. The industrial implementation process includes batching, roasting, leaching, purification, and lithium precipitation steps sequentially.

[0049] In step S4, the water and calcined clinker are mixed and stirred at a volume ratio of 1-6 mL / g to allow the water-soluble lithium sulfate to enter the aqueous phase. After leaching, a filter press, vacuum filter, or other solid-liquid separation equipment can be used for separation. The mother liquor containing lithium sulfate enters the subsequent purification process; the filter residue mainly retains the insoluble iron phosphate phase, the calcium-containing solid fluoride phase, and ash.

[0050] In step S5, an alkaline substance is gradually added while monitoring the pH, causing at least some aluminum and iron impurities to precipitate as hydroxides or basic salts, and causing some calcium impurities to form insoluble calcium salts or separate together with the residual suspended solids. The pH can be selected within the range of 7 to 11 depending on the level of impurities in the raw materials; considering both impurity removal, lithium loss, and alkali consumption, it is preferable to control it within the range of 8 to 11. When sodium hydroxide is used as the alkaline substance, to avoid premature precipitation of lithium carbonate leading to lithium loss, the pH is preferably not to exceed 10; when sodium carbonate is used as the alkaline substance, the pH can be adjusted within the range of 7 to 11. After solid-liquid separation, a purified lithium sulfate solution is obtained.

[0051] In step S6, a saturated sodium carbonate solution is added to a purified lithium sulfate solution, causing lithium carbonate to precipitate due to its low solubility at the corresponding temperature. After precipitation, the solution is filtered, and the resulting solid is washed with deionized water to reduce soluble impurities. The solid is then dried to obtain the lithium carbonate product.

[0052] Sampling, sample preparation, main content determination, and impurity determination of lithium carbonate products shall be performed in accordance with YS / T582-2023 "Battery Grade Lithium Carbonate". The main content of lithium carbonate (expressed as Li₂CO₃ mass fraction) shall be determined by acid-base titration or potentiometric titration, with two parallel determinations and the average value taken. Impurities such as potassium, sodium, calcium, magnesium, copper, lead, zinc, nickel, manganese, cadmium, aluminum, iron, sulfate, fluorine, and chlorine in the product can be determined by instrumental analysis methods such as inductively coupled plasma atomic emission spectrometry (ICP-OES). When using other methodologically validated analytical methods, quality control should be performed using certified reference materials or spiked recovery tests, and the detection limit, parallel sample deviation, and measurement results should be provided.

[0053] When the main content of lithium carbonate and all controlled impurities specified in YS / T582-2023 meet the requirements of the corresponding grade, the product is judged to be battery-grade lithium carbonate; if only the main content reaches 99.5% but other controlled impurities have not been tested, it is not judged to be battery-grade qualified. Figure 1 The lithium carbonate products mentioned refer to products obtained through lithium precipitation, washing, and drying, among which products that meet the relevant requirements of YS / T582-2023 are battery-grade lithium carbonate.

[0054] Example 1

[0055] One ton of spent lithium iron phosphate batteries was discharged, disassembled, crushed, and sieved, yielding 500 kg of black powder. Testing revealed that the black powder contained approximately 250 kg of negative electrode graphite and approximately 250 kg of positive electrode active material and electrolyte residues, including approximately 237.5 kg of lithium iron phosphate and approximately 12.5 kg of lithium hexafluorophosphate. The calculated total molar amount of lithium was approximately 1587 mol, and the total molar amount of fluorine was approximately 494 mol.

[0056] Add 1587 mol of anhydrous sodium sulfate (approximately 225.4 kg) according to a 1:1 molar ratio of lithium to anhydrous sodium sulfate; add 494 mol of light calcium carbonate (approximately 49.4 kg) according to a 1:1 molar ratio of fluorine to calcium carbonate. Dry mix the black powder, anhydrous sodium sulfate, and calcium carbonate in a high-speed mixer for 20 minutes to obtain a homogeneous mixture.

[0057] The mixture was fed into a rotary kiln and calcined at 600°C for 4 hours in air. After cooling, calcined clinker was obtained. Water was added at a volume ratio of 2 mL / g of calcined clinker, and the mixture was stirred and leached at 60°C for 30 minutes. The mixture was then filtered to obtain approximately 247 kg of filter residue and a mother liquor containing lithium sulfate. The residual carbon content of the calcined clinker, the phase composition of the filter residue, the total fluoride content, and the fluoride concentration of the leachate were determined according to the aforementioned testing methods.

[0058] Sodium carbonate was added to the mother liquor containing lithium sulfate to adjust the pH to 9, causing aluminum, iron, and some calcium impurities to precipitate or separate together with residual insoluble matter. The purified lithium sulfate solution was obtained after pressure filtration. Saturated sodium carbonate solution (1.1 times the theoretical volume) was added to the purified lithium sulfate solution, and the mixture was stirred and crystallized at 90℃ for 1 hour to precipitate lithium. After filtration, the mixture was washed with deionized water and dried at 120℃ to obtain the lithium carbonate product. Testing showed a total lithium recovery rate of 92.2% and a lithium carbonate content of 99.5%. The determination of battery-grade lithium carbonate was performed according to all items specified in YS / T 582-2023. The calcium and fluorine phases and fluorine fixation effect of the filter residue were evaluated using the aforementioned X-ray diffraction analysis, total fluoride determination, fluoride determination of the leachate, and fluorine elemental balance method.

[0059] The lithium leaching rate and fluorine fixation rate of the filter residue in Example 1 are as follows: Figure 3 As shown, the roasted clinker was leached with water at a ratio of 2 mL / g at 60 °C for 30 min. After solid-liquid separation and including the washing liquid in the leachate, the lithium leaching rate was calculated as 97.6% based on the ratio of the total mass of lithium in the leachate and washing liquid to the total mass of lithium in the roasted clinker entering the leaching process. The fluorine fixation rate of the filter residue was calculated as 96.5% based on the ratio of the mass of fluorine in the filter residue to the total mass of fluorine brought into the roasting-leaching system by the initial black powder. The lithium and fluorine contents were determined using the aforementioned detection methods, and the fluorine fixation rate of the filter residue was evaluated in conjunction with the phase analysis of the filter residue and the fluorine balance results.

[0060] As an example, when the water-to-material ratio is 2 mL / g, the mass fraction of lithium sulfate in the leachate is approximately 15.83%; when the water-to-material ratio is 3 mL / g, the mass fraction of lithium sulfate in the leachate is approximately 10.55% (both are percentages of lithium sulfate mass in the total mass of the leachate).

[0061] Example 2

[0062] The raw material preparation, batching, water leaching, and lithium precipitation operations in this embodiment are the same as in Example 1, except that the mixture is calcined at 500°C for 8 hours in air, and the pH of the lithium sulfate-containing mother liquor is adjusted to 7 during purification. Testing showed that the total lithium recovery rate was 95.1%, and the main lithium carbonate content was 98.5%. Under the conditions of 8 hours of calcination at 500°C, lithium conversion and recovery were achieved; the degree of carbon removal was quantitatively evaluated based on the total mass of the material before and after calcination and the total carbon mass fraction.

[0063] Example 3

[0064] The raw material preparation, batching, water immersion, and lithium precipitation operations in this embodiment are the same as in Example 1, except that the mixture is calcined at 650°C for 2 hours in air, and the pH of the lithium sulfate mother liquor is adjusted to 10 using sodium hydroxide. Testing showed that the total lithium recovery rate was 86.0%, and the main lithium carbonate content was 99.6%. The determination of battery-grade lithium carbonate was carried out according to all items specified in YS / T 582-2023. The pH of 10 is used to illustrate the operation method at a higher pH within the purification range when using sodium hydroxide. The removal degree of impurities such as aluminum and iron is evaluated by the liquid phase detection results before and after purification. Considering impurity removal, lithium loss, and alkali consumption, the pH is preferably controlled between 8 and 11.

[0065] The following examples illustrate the boundary values ​​and cross-combinations within the range of raw material composition, reagent ratios, and process parameters. Before operation, the black powder was sampled at multiple points, and the lithium, fluorine, and total carbon contents were measured. The amounts of anhydrous sodium sulfate and calcium carbonate added were then calculated based on the measured total molar amounts of lithium and fluorine. All percentages listed are based on the total mass of the black powder; the remaining components are current collector powder, conductive agent, binder, and other inorganic residues. The following examples do not list quantitative test results; their purpose is to disclose the operational process for the corresponding parameter combinations.

[0066] Example 4

[0067] A black powder was selected, comprising 30% positive electrode active material and residual fluorine electrolyte, 60% graphite, and 10% other components. Anhydrous sodium sulfate was added at 0.9 times the total molar amount of lithium, and calcium carbonate at 0.9 times the total molar amount of fluorine. After mixing for 20 minutes, the mixture was calcined at 500°C for 8 hours in air. After cooling, water was added at 3 mL / g, and the mixture was stirred and leached at 60°C for 30 minutes, followed by filtration. The pH of the mother liquor was adjusted to 7, and after impurity removal and filtration, the lithium precipitation, washing, and drying conditions described in Example 1 were followed.

[0068] Example 5

[0069] A black powder was selected, comprising 60% positive electrode active material and residual fluorine electrolyte, 20% graphite, and 20% other components. Anhydrous sodium sulfate was added at 1.2 times the total molar amount of lithium, and calcium carbonate at 1.2 times the total molar amount of fluorine. After mixing for 20 minutes, the mixture was calcined at 650°C for 2 hours in air. After cooling, water was added at 6 mL / g, and the mixture was stirred and leached at 60°C for 30 minutes, followed by filtration. The pH of the mother liquor was adjusted to 11, and after impurity removal and filtration, the lithium precipitation, washing, and drying conditions described in Example 1 were followed.

[0070] Example 6

[0071] A black powder was selected, comprising 40% positive electrode active material and residual fluorine electrolyte, 40% graphite, and 20% other components. Anhydrous sodium sulfate was added at 0.9 times the total molar amount of lithium, and calcium carbonate at 1.2 times the total molar amount of fluorine. After mixing for 20 minutes, the mixture was calcined at 550°C for 6 hours in air. After cooling, water was added at 5 mL / g, and the mixture was stirred and leached at 60°C for 30 minutes, followed by filtration. The pH of the mother liquor was adjusted to 9, and after impurity removal and filtration, the lithium precipitation, washing, and drying conditions described in Example 1 were followed.

[0072] Example 7

[0073] A black powder was selected, comprising 55% positive electrode active material and residual fluorine electrolyte, 30% graphite, and 15% other components. Anhydrous sodium sulfate was added at 1.2 times the total molar amount of lithium, and calcium carbonate at 0.9 times the total molar amount of fluorine. After mixing for 20 minutes, the mixture was calcined at 600°C for 4 hours in air. After cooling, water was added at 4 mL / g, and the mixture was stirred and leached at 60°C for 30 minutes, followed by filtration. The pH of the mother liquor was adjusted to 11, and after impurity removal and filtration, the lithium precipitation, washing, and drying conditions described in Example 1 were followed.

[0074] Implementation Result Analysis

[0075] Examples 1-3 show that, under the roasting conditions of air atmosphere, 500-650 °C, and 2-8 h, the total lithium recovery rate is 86.0%-95.1%, and the main lithium carbonate content is 98.5%-99.6%. Specifically, in Example 1, under the conditions of roasting at 600 °C for 4 h, leaching at 60 °C for 30 min at a water-to-material ratio of 2 mL / g, adjusting the pH of the leachate to 9, and precipitating lithium at 90 °C for 1 h, the total lithium recovery rate was 92.2%, the main lithium carbonate content was 99.5%, the lithium leaching rate was 97.6%, and the fluoride fixation rate of the filter residue was 96.5%.

[0076] Examples 4-7 provide the raw material composition, additive ratio, water-to-material ratio, and boundary values ​​and cross-combination operating conditions for the pH range. The fluoride fixation effect is comprehensively evaluated through phase analysis of the filter residue, determination of total fluoride in the filter residue, and fluorine elemental balance; elemental distribution is evaluated according to the aforementioned material balance method.

[0077] It should be noted that, in this document, the terms "comprising," "including," and any other variations are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or apparatus. Specific examples have been used in this document to illustrate the principles and implementation methods of the present invention. These examples are merely for the purpose of helping to understand the method and core ideas of the present invention. The above descriptions are only preferred embodiments of the present invention. For those skilled in the art, several improvements, modifications, or variations can be made without departing from the principles of the present invention, and the above technical features can be combined in an appropriate manner. These improvements, modifications, variations, or combinations, or the direct application of the concept and technical solution of the present invention to other situations without modification, should all be considered within the scope of protection of the present invention.

Claims

1. A method for selective lithium extraction and fluorine fixation via dry roasting of sodium sulfate and calcium carbonate, characterized in that, Includes the following steps: S1. Discharge, dismantle, crush and screen the waste lithium iron phosphate batteries to obtain black powder containing lithium iron phosphate, fluorine electrolyte residue and negative electrode graphite. S2. Determine the total molar amount of lithium and fluorine in the black powder, add anhydrous sodium sulfate at a molar ratio of lithium to anhydrous sodium sulfate of 1:(0.9~1.2), add calcium carbonate at a molar ratio of fluorine to calcium carbonate of 1:(0.9~1.2), and perform dry mixing to obtain a mixture; S3. The mixture is placed in a rotary kiln and calcined at 500-650°C for 2-8 hours under an oxidizing atmosphere to obtain calcined clinker. In this process, the graphite and organic matter in the black powder are oxidized, lithium is converted into water-soluble lithium sulfate, and fluorine is transferred to the calcium-containing solid phase. S4. The roasted clinker is subjected to water leaching and solid-liquid separation to obtain a mother liquor containing lithium sulfate and a filter residue containing a sparingly soluble iron phosphate phase, a calcium-containing and fluorine-containing solid phase and ash. S5. Add an alkaline substance to the mother liquor containing lithium sulfate and adjust the pH to 7-11 so that at least some of the aluminum, iron and calcium impurities form precipitates or are separated together with the residual insoluble matter. After solid-liquid separation, a purified lithium sulfate solution is obtained. S6. Add saturated sodium carbonate solution to the purified lithium sulfate solution to carry out lithium precipitation reaction. After solid-liquid separation, washing and drying, lithium carbonate product is obtained.

2. The method according to claim 1, characterized in that, In step S2, the molar ratio of lithium to anhydrous sodium sulfate is 1:1, and the molar ratio of fluorine to calcium carbonate is 1:

1.

3. The method according to claim 1, characterized in that, In step S3, the oxidizing atmosphere is air or oxygen-containing gas, the calcination temperature is 500~650℃, the calcination time is 2~8 hours, and during the calcination process, the negative electrode graphite and organic matter in the black powder are oxidized to reduce the residual carbon content of the calcined clinker.

4. The method according to claim 1, characterized in that, In step S4, the ratio of water volume to the mass of the roasted clinker is 1~6 mL / g, the leaching temperature is 40~80℃, and the leaching time is 20~60 minutes.

5. The method according to claim 1, characterized in that, In step S5, the alkaline substance is sodium carbonate, sodium hydroxide, or a combination of both, and the pH of the lithium sulfate-containing mother liquor is adjusted to 8-11.

6. The method according to claim 1, characterized in that, In step S6, the amount of saturated sodium carbonate solution added is 1.05 to 1.3 times the theoretical amount for lithium precipitation reaction. The theoretical amount for lithium precipitation reaction is calculated based on the measured total molar amount of lithium element in the purified lithium sulfate solution, with 1 mol of sodium carbonate corresponding to every 2 mol of lithium element. The lithium precipitation temperature is 80 to 95°C, and the lithium precipitation time is 0.5 to 2 hours.

7. The method according to claim 1, characterized in that, In the black powder obtained in step S1, the total mass of lithium iron phosphate and residual fluorine electrolyte accounts for 45% to 55% of the mass of the black powder, and the negative electrode graphite accounts for 40% to 55% of the mass of the black powder.

8. The method according to claim 1, characterized in that, In step S2, a high-speed mixer is used to dry mix the black powder, anhydrous sodium sulfate and calcium carbonate for 20 minutes to form a uniform mixture.

9. The method according to claim 1, characterized in that, It also includes X-ray diffraction analysis and fluorine element balance of the filter residue obtained in step S4 to evaluate the degree of fluorine transfer to the calcium-containing solid phase; the fluorine element balance includes the fluorine element in the initial black powder, filter residue, leachate and washing liquid, and when collectable dust and fluorine-containing tail gas are generated during the roasting process, it also includes the recovery of fluorine element in the dust and tail gas absorption liquid.

10. The method according to claim 1, characterized in that, In step S3, the roasting temperature is 600℃ and the roasting time is 4 hours; in step S4, the ratio of water volume to the mass of the roasted clinker is 2 mL / g, the leaching temperature is 60℃, and the leaching time is 30 minutes; in step S5, the pH is adjusted to 10; in step S6, the lithium precipitation temperature is 90℃, the lithium precipitation time is 1 hour, and the drying temperature is 120℃.

Citation Information

Patent Citations

  • A method for extracting lithium from waste lithium battery black powder by pressurized roasting to fix fluorine

    CN114132951B

  • Method for recovering lithium iron phosphate battery by roasting sulfate in air

    CN117185319A